Analysis of the performance of the Judicial Centers for Conflict Resolution in the light of the 2030 Agenda - Duarte, Júlia Garcia da Silva; Valério , Marco Aurélio Gumieri; Duarte, João Paulo Pereira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The National Judicial Policy for the Adequate Treatment of Conflicts of Interest (PJNTACI), developed by the National Council of Justice (CNJ), aims to disseminate the use of alternative methods of conciliation, mediation and conflict resolution, in order to make effective qualified access to justice, through the propagation of the culture of social pacification, which in turn, it is aligned with the basic principles set out by the Sustainable Development Goals (SDGs) pointed out by the UN. In this context, this paper seeks to analyze the alignment between the performance of the Judicial Centers for Conflict Resolution and Citizenship (Cejuscs) with SDG 16 which deals with "Peace, Justice and Effective Institutions" and SDG 10 which deals with "Reduction of inequalities". For this analysis, bibliographic research was carried out, with consultation of books, scientific articles, dissertations, theses and legislation. Based on the results pointed out by the analyses carried out, it is concluded that the Judicial Centers for Conflict Resolution act in accordance with the SDGs of the UN 2030 Agenda, since it provides for the resolution of legal issues between the interested parties, in a less conflictual way, in addition to exercising, free of charge, the technical services necessary for the processes of the assisted parties in question.